The Psychosocial Impact of Hypertension Diagnosis in Adult Patients: A Systematic Review - Arif Nurdiyanto; Arih Diyaning Intiasari; Siwi Pramatama Mars Wijayanti (STKIP Singkawang, 2026)
Hypertension is a non-communicable disease that often progresses silently but significantly affects the psychosocial well-being of adult patients. If unmanaged, it may lead to complications and decreased quality of life. This systematic literature review aims to explore the psychosocial impact of hypertension, both at the moment of diagnosis and throughout long-term management among adult patients. The study employed a systematic review method, following the PRISMA 2020 guidelines. Five primary quantitative studies published between 2015 and 2025 were analysed. The review was structured into two focal points: (1) psychological distress experienced upon diagnosis, and (2) chronic psychosocial stress in adults living with hypertension. The results showed that individuals with high psychosocial stress had an 8.198-fold higher likelihood of being diagnosed with hypertension. Contributing factors included poor sleep quality, low physical activity, and lack of social support. Additionally, prolonged distress such as anger, depression, and past trauma was significantly associated with poor blood pressure control, nonadherence to therapy, and decreased self-care. Patients with uncontrolled hypertension had a sixfold increased risk of experiencing hypertension-related distress. These findings highlight the urgency of integrating psychosocial screening and emotional support into routine hypertension management, especially at the primary care level.